1996
DOI: 10.1897/1551-5028(1996)015<2102:pctoss>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Chronic Toxicity of Sediments Spiked With Zinc: An Evaluation of the Acid-Volatile Sulfide Model Using a Life-Cycle Test With the Midge Chironomus Tentans

Abstract: Abstract-The development of sediment quality criteria for the cationic metals cadmium, copper, lead, nickel, and zinc has focused on the use of acid-volatile sulfide (AVS) as the primary normalization phase for predicting interstitial pore-water concentrations and bioavailability of the metals. To date, most of the research in support of AVS in this context has utilized short-term laboratory exposures, with a relative paucity of information pertaining to long-term exposures. The purpose of this study, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
92
1
6

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(118 citation statements)
references
References 37 publications
19
92
1
6
Order By: Relevance
“…At the end of the tests (43 days), average survival of the larvae in control sediments was approximately 14.8 % lower than that determined at 20 days, and similar phenomena have also been reported in two other studies using long-term life-cycle tests (Sibley et al 1996. The loss of midges between 20 days and the onset of pupation of the fourth-instar larvae was the reason for the increased mortality ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…At the end of the tests (43 days), average survival of the larvae in control sediments was approximately 14.8 % lower than that determined at 20 days, and similar phenomena have also been reported in two other studies using long-term life-cycle tests (Sibley et al 1996. The loss of midges between 20 days and the onset of pupation of the fourth-instar larvae was the reason for the increased mortality ).…”
Section: Resultssupporting
confidence: 84%
“…2). A similar phenomenon was also reported by Sibley et al (1996) in their zinc toxicity study. Assessing the rate at which emergence occurs may be more informative than relying entirely on total emergence, especially in situations of low-level contamination .…”
Section: Sublethal Toxicitysupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, a short metal-sediment equilibration time is typically employed in many studies, which can enhance partitioning of metals to porewater relative to sediment particles (J. S. Lee et al 2000). Partitioning coefficients typically decrease as the metal-sediment equilibration time increases , Sibley et al 1996, Leonard et al 1999). For example, Sibley et al (1996) reported that porewater Zn concentrations decreased up to 3 orders of magnitude at the end of 56 d equilibration, while [SEM -AVS] values varied only < 2 ×.…”
Section: Discussionmentioning
confidence: 99%